Penerapan Konsep Walkability Skala Manusia Berbasis Kegiatan Pelajar dalam Kawasan Pendidikan - Fariz Ryadi; Sri Pare Eni; Ramos P. Pasaribu (Syntax Corporation Indonesia, 2024)
Walkability is one part of realizing sustainable and livable city planning and design. The education area is one of the areas in urban areas that has a complex and dynamic level of problems. The attraction of the educational function in an area causes a high movement of people and goods so that in its development various commercial functions grow in it. The M.A Turungku road corridor is part of the education area in Buol City. In the corridor there are various educational functions starting from the elementary, secondary, to upper levels. The pull of the existence of the educational function in the M.A Turungku road corridor has resulted in the growth of commercial functions followed by its impact on the decline in environmental quality. The decline in the quality of the physical environment that occurs in the M.A Turungku road corridor has an impact on the comfort of walking activities, especially for students in the corridor. Therefore, in this study, the improvement of walkability in the M.A Turungku road corridor will be studied through a human-scale approach based on student activities. The research approach uses a rationalistic approach with data collection techniques through systematic observation. The results of this study show that the comfort level of human sensing when walking on the M.A Turungku road corridor gets an uncomfortable value. Meanwhile, in the results of the analysis of pedestrian movements and behavior, during the day in segment 2 of the M.A Turungku road corridor, outdoor activities occur very dynamically where main activities, additional activities, and follow-up activities of pedestrians are formed.